1999
DOI: 10.1128/jvi.73.12.10514-10518.1999
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Latent Varicella-Zoster Virus and Herpes Simplex Virus Genomes in Human Trigeminal Ganglia

Abstract: Using real-time fluorescence PCR, we quantitated the numbers of copies of latent varicella-zoster virus (VZV) and herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) genomes in 15 human trigeminal ganglia. Eight (53%) and 1 (7%) of 15 ganglia were PCR positive for HSV-1 or -2 glycoprotein G genes, with means of 2,902 ± 1,082 (standard error of the mean) or 109 genomes/105 cells, respectively. Eleven of 14 (79%) to 13 of 15 (87%) of the ganglia were PCR positive for VZV gene 29, 31, or 62. Pooling of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…Likewise, the study of new and emerging viruses has been ideally complemented by the use of homogeneous real-time PCR assays as tools to demonstrate and strengthen epidemiological links between unique viral sequences and the [177,234,240,253,254,266,267,280,284,292,294] Solid tissues [172,198,238,[256][257][258]271,288,295] Cerebrospinal fluid [136,190,192,194,248] Peripheral blood mononuclear cells [183] Bone marrow [120] Whole blood [179,291] Plasma [118] Serum [171,172,180,279,287] Swabs [192,259,296] Bronchoalveolar lavage [243,246] Amniotic fluid [286] Saliva and sputum [158,233] Faeces [264,285] Urine [12,…”
Section: Virusesmentioning
confidence: 99%
“…Likewise, the study of new and emerging viruses has been ideally complemented by the use of homogeneous real-time PCR assays as tools to demonstrate and strengthen epidemiological links between unique viral sequences and the [177,234,240,253,254,266,267,280,284,292,294] Solid tissues [172,198,238,[256][257][258]271,288,295] Cerebrospinal fluid [136,190,192,194,248] Peripheral blood mononuclear cells [183] Bone marrow [120] Whole blood [179,291] Plasma [118] Serum [171,172,180,279,287] Swabs [192,259,296] Bronchoalveolar lavage [243,246] Amniotic fluid [286] Saliva and sputum [158,233] Faeces [264,285] Urine [12,…”
Section: Virusesmentioning
confidence: 99%
“…The genes encoding HSV-1 and HSV-2 glycoprotein G were selected for HSV type-specific real-time PCR. The sequences of the primers and probes used for these experiments were described by Pevenstein et al [1999]. PCR reactions were performed using the TaqMan PCR Kit (PE Applied Biosystems, Foster City, CA) according to the manufacturer's directions.…”
Section: Real-time Pcr For Hsv-1 and Hsv-2mentioning
confidence: 99%
“…Recent studies have suggested that the detection of HSV DNA by polymerase chain reaction (PCR) increases the sensitivity of detection relative to antigenic detection or cell culture methods [Cone et al, 1991[Cone et al, , 1994Lakeman and Whitley, 1995;Kimberlin et al, 1996;Mitchell et al, 1997]. While quantitative analysis of viral DNA by real-time PCR may become a valuable tool for bedside monitoring of HSV infection and progression [Pevenstein et al, 1999;Ryncarz et al, 1999;Espy et al, 2000;Kessler et al, 2000;Aldea et al, 2002;Ndjoyi-Mbiguino et al, 2003;Asano et al, 2004], it is not yet common in hospital laboratories due to the requirement of specific expensive equipment (a thermal cycler).…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative system was developed recently to measure the genome copies of HSV using a real-time PCR assay . This assay allows quantitation of HSV DNA accurately and reproducibly over a wide linear range [Pevenstein et al, 1999;Ryncarz et al, 1999;Ito et al, 2000]. It seems reasonable that estimation of the viral load could be used prognostically to help predict the likely course of neonatal HSV infection.…”
Section: Introductionmentioning
confidence: 99%